The crossroads of contemporary sociology and the crisis of its subject and vocational identity - Mitrović, Ljubiša (Sociološki pregled, 2021)
Contemporary sociology is at a fateful crossroads. The paper points to some aspects of its crisis as a science and vocation, the forms of its cognitive pathology and the erosion of positive identity in the universe of sciences and the modern professional division of labour. Indicating the causes and consequences of this crisis, the author concludes that it cannot be overcome only by technical improvement of the methodology of empirical research, but requires profound efforts of the new generation of sociologists, and new answers. Otherwise, Peter Berger’s pessimistic predictions about the obsolescence and bankruptcy of sociologists and sociologists might come true. The conclusions we reached in our problematization of this issue can be summarized as follows: 1) the need to redefine contemporary sociology in the spirit of globalization of its subject as a multicomplex science of the laws of structure and dynamics of the global world system and the theoretical-empirical study of phenomena and processes at all levels of social organization. macro, meso, micro) from the perspective of the methodological principle of dialectical concrete totality; 2) building a new theoretical synthesis in the form of a multidisciplinary integrated paradigm; 3) opening sociology through multidisciplinary and transdisciplinary research towards new challenging fields of the future that has begun; 4) redefining its vocation identity in the Mils-Bourdieu key as a martial discipline, radical-critical, reflexive-engaged, emancipatory and actionist sociology.